Barriers and Pathways to Providing Long‐Acting Reversible Contraceptives in Massachusetts Community Health Centers: A Qualitative Exploration. Issue 3 (25th June 2018) - Janiak, Elizabeth; Clark, Jill; Bartz, Deborah; Langer, Ana; Gottlieb, Barbara
Abstract : CONTEXT: Structural barriers to the provision of long‐acting reversible contraceptive (LARC) methods at community health centers have been identified in quantitative research, but the processes and behaviors by which center staff respond to these barriers are poorly understood. METHODS: Focus group discussions were conducted with clinical, support and administrative staff at three Massachusetts community health centers between April 2014 and January 2015. The centers were purposively selected to constitute a sample with diverse characteristics. Overall, 57 individuals participated in seven focus groups. Data were analyzed inductively using a modified grounded theory approach, and typical pathways to obtaining LARC methods were identified. RESULTS: Community health center staff provided contradictory descriptions of their facilities' protocols and practices. Patients' pathways to obtaining LARC methods were idiosyncratic and clinician‐dependent, and resulted in patients' waiting between one week and three months to receive their preferred method. Providers' individual comfort with and perceived competence in contraceptive counseling often shaped patients' pathways to care. Overall, staff did not consider same‐day insertion of LARC methods a feasible goal. Counseling protocols, insurance verification practices and logistical challenges in ordering and stocking devices were identified as major barriers to timely placement. CONCLUSIONS: Efforts to improve LARC provision at community health centers should include the education of staff in how expeditious placement constitutes clinical best practice and the implementation of infrastructural changes to support staff in efficiently counseling patients, scheduling placements and procuring LARC devices regardless of patients' insurance coverage.